TYPING SPEED TEST: INNOVATION IN TYPING SPEED MEASUREMENT FOR OFFICE MANAGEMENT STUDENTS IN THE INDEPENDENT CURRICULUM - Dharma, Buyung Adi; Basuki, Andi; Churiyah, Madziatul; Sakdiyyah, Dewi Ayu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study aims to develop and evaluate an artificial intelligence (AI)-based typing speed test platform for Office Management program students in the Merdeka Curriculum. In the ever-evolving digital era, fast and accurate typing skills are becoming increasingly important both in the workplace and in education. This study follows the Research & Development method with five main steps: initial research, product development, expert validation, small-scale and large-scale trials. The developed platform, called the Typing Speed ​​Test, is designed to provide real-time feedback, performance analysis, and personalized exercises based on user abilities. The trial involved 150 students from various schools in East Java, showing positive results with 90% of students reporting significant improvements in their typing skills. The platform is considered effective in improving typing speed and accuracy and supports the principles of the Merdeka Curriculum which emphasizes independent learning and the development of 21st-century competencies. The integration of AI into the platform allows for dynamic adaptation of learning, making it a modern solution that can be easily integrated into the educational curriculum. The findings of this study emphasize the importance of digital literacy and the potential of AI in providing innovative and effective learning experiences to prepare students for the demands of an increasingly technology-dependent workforce